Maternal Serum Zinc Level Is An Independent Factor For Infant Birth Weight, But Not For Preterm Delivery - Demirtürk, Fazlı; Aytan, Hakan; Çalışkan, Ahmet (Gynecology Obstetrics & Reproductive Medicine, 2006)
OBJECTIVE: To compare the maternal zinc levels in patients suffering from preterm delivery and women with term pregnancies and to assess the effect of maternal serum zinc levels on birth weight. STUDY DESIGN: 50 preterm laboring pregnant women (mean age 23.92 ± 5.17 years) and 20 term pregnants (mean age 26.40 ± 4.98 years) were enrolled. Serum zinc levels were measured with “flamed atomic absorption technique”. Gestational age, birth weight, Apgar scores of the first and fifth minutes, socioeconomic status and smoking habits were evaluated. RESULTS: The mean value of serum zinc levels was 1.10 ± 0.23 μg/ml in the control group and 0.35 ± 0.10 μg/ml in the preterm group. Birth weight, Apgar scores of the first and fifth minutes, gestational ages and serum zinc levels were found to be significantly lower in preterm group (p<0,001). Maternal serum zinc level was found to be correlated with gestational age and birth weight; however, the correlation of zinc with gestational age disappeared when regression analysis was applied and zinc was found to be an independent factor affecting birth weight. Zinc levels less than 1 μg/ml had a sensitivity of 100%, specificity of 70%, positive predictive value of 89.9% and negative predictive value of 100% for preterm labor in this study. CONCLUSION: Maternal serum zinc level is linearly correlated with birth weight and tends to be lower in preterm deliveries, although not an independent factor.